CLINICAL STUDY OF IMIPENEM/CILASTATIN SODIUM PART II: THE EFFECT OF IMIPENEM/CILASTATIN SODIUM ON PLATELET FUNCTION AND BLOOD COAGULATION - NAKAGAMI, KAZUKIYO; SUZUKI, HAJIME; NOGUCHI, EISEI; AKIZAWA, TAKANORI; TERADA, HIDEO (CHEMOTHERAPY, 1989)
Recently, a tendency to bleed as a side effect of antibiotics has been given attention. We studied the effect of imipenem/cilastatin sodium (IPM/CS), a carbapenem antibiotic which belongs to a new class of beta-lactam agents, on platelet function and blood coagulation. The subjects were 11 patients with respiratory infections: 10 with pneumonia and 1 with pulmonary suppuration. IPM/CS was administered by i. v. drip at a dose of 1 g/day for 7 days, and the following parameters measured before and after treatment: platelet count, bleeding time, platelet adhesiveness, platelet aggregation, platelet ATP release, prothrombin time, active partial thromboplastin time, serum fibrinogen, fibrin degradation products, thrombo test and clotting factors II·VII·IV·V. There was no deterioration in the platelet function or blood coagulation tests after administrations of IPM/CS. We therefore concluded that IPM/CS is a safe antibiotic in regard to platelet function and blood coagulation.